Centrifugally automated Solid-Phase Extraction of DNA by immiscible liquid valving and chemically powered centripetal pumping of peripherally stored reagents - David J. Kinahan (Elsevier, 2021)
This paper presents two flow-control technologies for use on centrifugal Lab-on-a-Disc systems. The first, immiscible liquid valving, selectively blocks microfluidic channels using a high-density liquid fluorocarbon (FC-40). Used with a specific channel geometry, the FC-40 can permit liquid to enter a chamber but prevents it flowing back along the same path and so acts as “liquid” check-valve. The same liquid can be combined with a water-dissolvable film to provide an extremely robust liquid routing structure. The second technology uses CO2 gas, created by wetting of commodity baking powder by water, to centripetally pump liquid from the periphery of the disc to the centre of the disc. The technologies are combined with valving schemes based on strategically placed, solvent-selective dissolvable films (DFs) to demonstrate repeated pumping of a liquid sample from the edge of the disc to the centre of the disc. The flow-control technologies are then combined to demonstrate fully automated Solid-Phase Extraction (SPE) of DNA with reagent storage on the periphery of the disc. We report an extraction efficiency of 47% measured relative to commercial spin-columns.